2021
DOI: 10.1111/1462-2920.15400
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glutamine synthetase activity by transcriptional and posttranslational modifications negatively influences ganoderic acid biosynthesis in Ganoderma lucidum

Abstract: Summary Glutamine synthetase (GS), a central nitrogen metabolic enzyme, plays important roles in the nitrogen regulation network and secondary metabolism in fungi. However, the mechanisms by which external nitrogen sources regulate fungal GS activity have not been determined. Here, we found that GS activity was inhibited under nitrate conditions in Ganoderma lucidum. By constructing gs‐silenced strains and adding 1 mM GS inhibitor to inhibit GS activity, we found that a decrease in GS activity led to a decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…In plants, bacteria, and animals it is widely accepted that the GlnS is regulated at the level of transcription, posttranscription, translation, and post translation. Though little is known about the regulatory mechanism of GlnS activity in fungi [ 43 ], one of those mechanisms might be the reason why we could not detect GlnS activity in P. sedebokerense . We thus searched for the GlnS gene in the draft genome (unpublished) of our P. sedebokerense strain.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…In plants, bacteria, and animals it is widely accepted that the GlnS is regulated at the level of transcription, posttranscription, translation, and post translation. Though little is known about the regulatory mechanism of GlnS activity in fungi [ 43 ], one of those mechanisms might be the reason why we could not detect GlnS activity in P. sedebokerense . We thus searched for the GlnS gene in the draft genome (unpublished) of our P. sedebokerense strain.…”
Section: Resultsmentioning
confidence: 89%
“…We failed to detect fungal GlnS enzyme activity, although we used different assays. Little is known about the regulatory mechanism of GlnS activity in fungi; however, it was recently shown that transcriptional and posttranslational modifications are involved in the regulation of GlnS activity in the fungus Ganoderma lucidum [ 43 ]. We assume that in P. sedebokerense, GlnS is active during a specific growth stage which we could not identify yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated with 1 ml of RNAiso Plus (TaKaRa) from 50 mg fresh mycelia and subsequently reverse transcribed to cDNA with a PrimeScript RT reagent kit (TaKaRa). Gene expression analysis was performed by qRT‐PCR according to a previous method (Zhu et al, 2021). The expression levels of the spds1 , spds2 , pao , odc and Glmyb genes under different heat stress times were analysed with 18S rRNA used as an internal standard gene (primers listed in Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…These enzymes enable the initial N incorporation to the amino acids Gln, Glu, Asn, and Asp assimilation, but also GS has been identified as targets of nitration (Lozano-Juste et al, 2011). GS enzymes from mammals and fungi seem to be nitrated and inactivated, thus affecting the metabolism of Glu and ammonia in liver (Frieg et al, 2021) and the secondary metabolism in fungi (Zhu et al, 2021), respectively. Plant GDH seem to be involved mainly in Glu oxidation to supply cells with carbon skeletons under carbon limiting conditions (Robinson et al, 1991).…”
Section: Nitration Of the Enzymes Of Nitrate Assimilation And No Bios...mentioning
confidence: 99%